Sejarah Perkembangan DSN MUI dan Istinbath Hukum - Gusti Haitsam (Majelis: Jurnal Hukum Indonesia, 2025)
The Indonesian Ulema Council (MUI) has a very important role in providing religious and social guidance for Muslims in Indonesia. The history of the MUI began in 1975, with the aim of strengthening the unity of Muslims and issuing fatwas in accordance with Islamic teachings. Over time, the MUI has developed into a very influential institution in determining religious policies in Indonesia. One of the main commissions in the MUI is the Fatwa Commission, which is tasked with issuing fatwas related to current religious issues, especially in facing the challenges of the times and social problems that continue to develop. This study aims to explore the urgency of the role of the MUI Fatwa Commission in issuing fatwas that are in accordance with the needs of the Indonesian people. In addition, this study also discusses the istinbath method applied by the MUI Fatwa Commission in issuing fatwas, as well as its application to contemporary issues. This istinbath method refers to the process of deriving law from the main sources of Islam, such as the Qur'an, Hadith, Ijma', and Qiyas, taking into account the existing social context and dynamics. The results of the study show that the MUI Fatwa Commission has a very great urgency in responding to various problems of Muslims, especially those related to modern issues such as sharia economics, technology, and health issues. Through the istinbath method, the MUI has succeeded in providing fatwas that are not only based on classical texts, but are also relevant to current developments. For example, in the matter of sharia economics, the MUI has issued a fatwa that supports the sharia financial system while still paying attention to the applicable fiqh rules.